Clinical correlation and survival analysis of hepatitis B virus infection in oral squamous cell carcinoma: a retrospective study of 1373 patients - Rukeng Tan; Yiyao Zhu; Zengyu Chen; Xinkai Feng; Yujie Liang; Sien Zhang; Nuerbiya Abuduxiku; Guiqing Liao; Le Yang (BMC Cancer)
Abstract Background Chronic hepatitis B virus (HBV) infection poses a significant global public health challenge and is found closely related to extrahepatic cancers, including head and neck cancer. Oral squamous cell carcinoma (OSCC) is the major category of head and neck cancer. This retrospective study was conducted to explore the clinical correlation and survival analysis of OSCC patients with HBV. Methods The study involved 1,373 patients with OSCC treated at the Hospital of Stomatology, Sun Yat-sen University from 2012 to 2022. Propensity score matching was used to analyze the clinical correlations and survival outcomes, specifically overall survival (OS) and disease-free survival (DFS), in patients with or without hepatitis B surface antigen (HBsAg) seropositivity. Subgroup analyses were conducted for both the early and advanced stages of OSCC. The benefits of neck dissection in OSCC patients with HBV infection were further investigated. Results The prevalence of HBV infection in our cohort was 12.0%. The HBsAg (+) group had a higher percentage of individuals under 60 (73.3% versus 63.7%, p = 0.016). Post-matching for age, sex, pathological T category, pathological N category, and neck dissection, the OSCC patients with HBsAg (+) had lower 5-year OS and DFS rates rather than HBsAg (−) patients, especially those with advanced stage and cervical lymph node metastasis. HBsAg (−) was confirmed as an independent protective prognostic indicator for both OS (hazard ratio [HR] = 0.52; 95% confidence interval [CI] = 0.34–0.79; p = 0.002) and DFS (HR = 0.69, 95% CI = 0.50–0.96; p = 0.027). Notably, elective neck dissection was recognized as an independent protective factor influencing 5-year OS and DFS. While DOI and pathological N category were both confirmed as the risk factors for prognosis. Conclusions HBsAg is a potential prognostic marker for OSCC. It is essential to screen for HBV infection prior to initiating tumor treatment. Additionally, serological testing, antiviral prophylaxis and therapy play crucial roles in preventing HBV reactivation during the course of tumor treatment. In cases of early OSCC associated with HBV infection, elective neck dissection has been shown to reduce the rates of recurrence and metastasis significantly.